2019
DOI: 10.1136/bmjhci-2019-000019
|View full text |Cite
|
Sign up to set email alerts
|

Dietitians can improve accuracy of prescribing by interacting with electronic prescribing systems

Abstract: BackgroundDietitians increasingly interact with electronic health records (EHRs) and use them to alert prescribers to medication inaccuracies.ObjectiveTo understand renal dietitians’ use of electronic prescribing systems and influence on medication accuracy in inpatients. In outpatients to determine whether renal dietitians’ use of the electronic medication recording might improve accuracy.MethodsIn inpatients we studied the impact of dietetic advice on medical prescribing before and after moving from paper re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…GPs in our study commonly reported a lack of communication regarding ONS prescriptions commenced elsewhere, more specifically in the patients' transition from the hospital to the community which could lead to ONS passively continued with no revision. A recent UK study found that the involvement of renal dietitians in reviewing and making recommendations on an online prescription system to update patients medications resulted in an improvement on the accuracy of the medication lists [52]. The entry of recommendations to the electronic health record by dietitians also resulted in a greater number of patients receiving their dietetic treatment.…”
Section: Supporting Statements From the Csrmentioning
confidence: 99%
“…GPs in our study commonly reported a lack of communication regarding ONS prescriptions commenced elsewhere, more specifically in the patients' transition from the hospital to the community which could lead to ONS passively continued with no revision. A recent UK study found that the involvement of renal dietitians in reviewing and making recommendations on an online prescription system to update patients medications resulted in an improvement on the accuracy of the medication lists [52]. The entry of recommendations to the electronic health record by dietitians also resulted in a greater number of patients receiving their dietetic treatment.…”
Section: Supporting Statements From the Csrmentioning
confidence: 99%
“…The system is designed to minimise medication related errors via various automatic rule-based prescribing checks. Previous studies have successfully used similar information systems to understand nature of errors and communications amongst healthcare professionals around prescribing decisions and mitigating errors [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…For example, dietitians in the United Kingdom (UK) and New Zealand (NZ) have formally recognised advanced and extended practice pathways. These pathways, which include prescribing of oral nutritional supplements, or interaction with electronic prescribing systems, support physicians to minimise poor prescribing practices, 5,6 thereby potentially overcoming challenges associated with waiting times and healthcare costs, and poor patient care 3,7,8 . A 2015 review regarding extended prescribing across the UK, accounted for training costs, backfill of staff to attend training, benefits of improved health outcomes and associated decreased health costs, and also non‐monetised costs such as clinical supervision 9 .…”
Section: Introductionmentioning
confidence: 99%